Dystonia and Hypoparathyroidism - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1988)
Recurrent attacks of flexion of the right hand and arm and bowing of the head initiated by sudden movement were associated with idiopathic hypoparathyroidism in a 12 yr old boy seen at the Children's Hospital of Philadelphia, PA.